2022
DOI: 10.1126/science.abg7985
|View full text |Cite
|
Sign up to set email alerts
|

Convergent selection of a WD40 protein that enhances grain yield in maize and rice

Abstract: A better understanding of the extent of convergent selection among crops could greatly improve breeding programs. We found that the quantitative trait locus KRN2 in maize and its rice ortholog, OsKRN2 , experienced convergent selection. These orthologs encode WD40 proteins and interact with a gene of unknown function, DUF1644, to negatively regulate grain number in both crops. Knockout of KRN2 in maize or OsKRN2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 84 publications
0
74
0
Order By: Relevance
“…Ear traits, kernel number per row (KNPR) and kernel row number (KRN), of maize have been concerned by researchers (Matsuoka et al, 2002 ; Chen et al, 2021 , 2022 ; Ning et al, 2021 ), however, the influence of ear architecture on drought resistance is not well understood. In this study, we obtained 27 hybrids with the stubby or slender ears and applied manual pollination, including continuous and synchronous pollination, to observe the silking dynamics and evaluate drought resistance in two ear types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ear traits, kernel number per row (KNPR) and kernel row number (KRN), of maize have been concerned by researchers (Matsuoka et al, 2002 ; Chen et al, 2021 , 2022 ; Ning et al, 2021 ), however, the influence of ear architecture on drought resistance is not well understood. In this study, we obtained 27 hybrids with the stubby or slender ears and applied manual pollination, including continuous and synchronous pollination, to observe the silking dynamics and evaluate drought resistance in two ear types.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the breeder is less aware of the relationships between ear architecture and drought resistance, they pay close attention looking at genes that control ear length and kernel row number, potentially valuble to improve ear architecture (Bommert et al, 2013 ; An et al, 2019 ; Du et al, 2021 ; Ning et al, 2021 ). Especially in recent years, great progress has been made in the study of controlling genes for ear traits (Du et al, 2021 ; Ning et al, 2021 ; Chen et al, 2022 ). In their studies, increases in ear length or kernel row number significantly promoted the yield per ear, but maize plants have limited photosynthetic capacity, especially under stress, which means that the kernel number cannot increase indefinitely.…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes exhibited high DNA sequence similarity with already reported genes in rice, which are involved in the regulation of both spikelet development and stem growth [ 65 , 66 , 67 ], including OsSLRL1 homolog gene TraesCS3A02G233000/TraesCS3B01G262400 and OsEATB homolog TraesCS5B02G315500/TraesCS5A02G314600 ( Figure 5 B,C). KRN2 and OsKRN2 genes in rice and maize have recently been reported to enhance the yield of both crops through editing the promoter region [ 72 ]. A ~4-kb substitution in the promoter region of core TF TomLoxC resulted in a change of the tomato flavor [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutants of An-1 ( Awn-1 ) and An-2 showed reduced awn length, increased GN and GW, and these genes have experienced artificial selection during rice domestication ( Luo et al, 2013 ; Gu et al, 2015 ). Furthermore, recent study revealed that OsKRN2 ( Kernel Row Number 2 ), which negatively regulates GN, has undergone convergent selection with its maize ortholog KRN2 during the domestication of rice and maize ( Chen et al, 2022 ). These findings partially revealed the genetic basis and molecular mechanisms underlying the selective forces of GN and other domestication related traits.…”
Section: Introductionmentioning
confidence: 99%